Legality and Legal Order as Social Criteria of Legal Culture of Society: Theoretical Aspect - I. A. Demidova (Сибирское юридическое обозрение, 2021)
The Author proceeds from the fact that in modern political and legal realities, the most important social indicator of the legal culture of society is the state of legality, which contributes to ensuring the legal functioning of state and public institutions, guarantees of the rights and interests of the individual. The aim of the study is to analyze theoretical provisions regarding legality and law and order in the context of designating them as criteria of legal culture - signs on the basis of which it is possible to assess the formation of legal culture at the level of society.The degree of scientific elaboration of the problems of legality and legal order in the works of Russian and Belarusian jurists of the Soviet and modern periods has been determined. This made it possible to establish the generic commonality of law and order as a basic theoretical setting, which manifests itself in considering them as different sections of the ordering of social relations. Legality is investigated as a principle, method and, at the same time, a mode of state-power activity. The conditions for ensuring the legal order establish the exact and unswerving implementation of legal prescriptions by all subjects of law, which characterizes their legal culture. The theoretical model of the mechanism for ensuring the rule of law and legal order is presented through the characteristics of its social and legal content, subject composition and institutional and functional structure.The role of legal law and legal principles in ensuring the rule of law and legal order is shown. The subsystems of the institutional and functional structure of the mechanism for ensuring the latter – regulatory, state power, guarantees for the implementation of legal provisions – are analyzed. The  political, legal, organizational and scientific principles of the functioning of  the mechanism for ensuring the legal order are outlined. The following types of legal order are determined: civil, international, state (constitutional). Taken together, all types of legal order are interconnected, which reflects the universality of law as a social regulator, the importance of its principles. This  circumstance determines the legal criteria for the uniformity of legal  regulation of social relations, generally accepted international legal standards in the field of human rights.The directions of improving the legal culture of society are determined by high-quality rule-making; effective functioning of all government agencies, primarily law enforcement agencies; implementation of social and legal guarantees of legality and legal order.